2006
DOI: 10.4141/s05-021
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient supply from organic amendments applied to unvegetated soil, lettuce and orchardgrass

Abstract: . Nutrient supply from organic amendments applied to unvegetated soil, lettuce and orchardgrass. Can. J. Soil Sci. 86: 21-33. Organic sources of nutrients are increasingly being used in horticultural and certified organic production. The nutrient-supplying potentials of poultry manure compost (PM), feather meal (FM), alfalfa meal (AA) and vermicastings (VC) and an unamended control were measured in a growth room experiment. The amendments were applied at rates equivalent to 200, 400 and 800 kg total N ha -1 to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
15
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 36 publications
2
15
0
1
Order By: Relevance
“…Similarly, the declines for pots treated with 0, 33.33, 66.67 and 100% of the recommended doses of NPK from inorganic fertilizers at this stage were 48, 51, 53 and 56%, respectively. This trend has also been reported by Hammermeister et al (2006), who reported lower soil N mineral content in the final analysis compared to the initial analysis for several treatments, suggesting loss of N with time. Similarly, Nathiya and Sanjivkumar (2015) have also found higher available nitrogen content on vegetative and flowering stage of groundnut than at postharvest stage, indicating that plants derive nutrients from soil for their growth and development leading to the depletion of soil nutrients at the late growth stages.…”
Section: Total Nitrogen (Mg Kg -1 ) Content Of the Soil At Different supporting
confidence: 85%
See 1 more Smart Citation
“…Similarly, the declines for pots treated with 0, 33.33, 66.67 and 100% of the recommended doses of NPK from inorganic fertilizers at this stage were 48, 51, 53 and 56%, respectively. This trend has also been reported by Hammermeister et al (2006), who reported lower soil N mineral content in the final analysis compared to the initial analysis for several treatments, suggesting loss of N with time. Similarly, Nathiya and Sanjivkumar (2015) have also found higher available nitrogen content on vegetative and flowering stage of groundnut than at postharvest stage, indicating that plants derive nutrients from soil for their growth and development leading to the depletion of soil nutrients at the late growth stages.…”
Section: Total Nitrogen (Mg Kg -1 ) Content Of the Soil At Different supporting
confidence: 85%
“…Even though chemical fertilizers substantially increased the available plant nutrients during the first weeks, losses arising from different factors limit the continual supply of nutrients at critical periods where plants inquire high demand for these nutrients. Reports from Hammermeister et al (2006) show that chemically fertilized plots declined in NH 4 + as sampling time continues. On the other hand, available P was high at tillering which declined later at flowering and maturity stages of rice (Lungmuana et al, 2013) compared to organic residues and manures.…”
Section: Introductionmentioning
confidence: 99%
“…In a lettuce (Lactuca sativa L.) pot study, of the total N applied (200-800 kg · ha -1 ), available N over 6 months was 50% to 70% with feather meal and poultry manure compost treatments, 10% to 40% with alfalfa meal, and 10% with vermicastings. Application rates above 800 kg · ha -1 did not result in corresponding increases in nutrient supply (Hammermeister et al, 2006). Insufficient soil N availability is frequent in organic vegetable production because of unpredictable N release.…”
mentioning
confidence: 88%
“…Compared with conventional agriculture, nutrient management in organic farming rotations can become very complex when trying to account for nutrient contributions from soil amendments, in addition to forages. Considerable efforts have been made to evaluate N availability for different types and rates of soil amendment (N'Dayegamiye et al 1997;Eghball 2000;Mkhabela and Warman 2005;Hammermeister et al 2006) and forages (Patriquin et al 1986;Griffin and Hesterman 1991). On a commercial farm, the application rates of soil amendments are also adjusted according to expected nutrient availability from previous crops in rotation and the nutrient demands of the current crop.…”
mentioning
confidence: 99%
“…The amounts of N 2 fixed by leguminous crops are affected by environmental conditions (Haase et al 2007), and a large variation in fixation rates (i.e., from 40 to 240 kg N ha (1 ) has been reported (Patriquin et al 1986;Griffin and Hesterman 1991). Nitrogen availability from soil amendments can also vary depending on N source (Eghball 2000;Amlinger et al 2003;Hammermeister et al 2006), and application rate (He´bert et al 1991). Nitrogen management could be improved by quantifying the N availability from soil amendments and forages at the end of an organic transition period.…”
mentioning
confidence: 99%